PEMANFAATAN PASIR PANTAI DAN FLY ASH PADA KINERJA PAVING BLOK - Karaeng, Immanuel (BANDAR: JOURNAL OF CIVIL ENGINEERING, 2024)
Paving blocks are a building material that is often used in the world of construction. The use of Fly ash and Bottom ash in this research adopted an experimental research method that went through several tests, namely compressive strength, absorption and porosity tests. The mixture of fly ash and bottom ash used in each test object is 0%, 10%, 20%, 30%, 40% and 50%. The results of this research are results that have gone through the testing stages as regulated in SNI 03-0691-1996 concerning paving blocks. This research aims to determine the average value of the compressive strength test at 100 days, absorption city test at 94 days, and porosity test at 96 days. The results of this research in terms of the Fly Ash mixture show the best results from this test, namely the FA-PP3 variation with a compressive strength value of 14.29 Mpa, water absorption of 10.38% and porosity of 18.22%. Meanwhile, the best results for the Bottom Ash mixture showed that the compression test results were BN-PP3 14.19 Mpa, absorption capacity 11.231%, and porosity 20.211%. This research concludes that the compressive strength at 100 days still needs to be improved, and some samples do not have to meet the standard deviation requirements in accordance with SNI 03-0691-1996 concerning paving blocks